Big data security - Banerjee, Indradip; Bhattacharyya, Siddhartha, 1975-; Gupta, Shibakali (De Gruyter frontiers in computational intelligence ;, 2019)
After a short description of the key concepts of big data the book explores on the secrecy and security threats posed especially by cloud based data storage. It delivers conceptual frameworks and models along with case studies of recent technology